Three-body wear of different composites resins - Homayoun Alaghehmand; Abdolhamid Alhavaz; Mohammad Masoumi (Babol University of Medical Sciences, 2012)
Introduction: Low resistance of composite resins to abrasion is a primary concern in the application of these materials for posterior restorations which are prone to high occlusal loads. This study compared the wear resistance of three types of composites. Methods: In this laboratory experiment, five specimens of each of the three types of composites (z250, Heliomolar, Opallis) were prepared separately in brass molds. Composites were placed in 1-mm layers and were cured for 40 seconds. Using an abrasive device, Pedeb 1, with a chrome-cobalt abrasor, the specimens were abraded under a 20-MPa force, after 5000, 20000, 40000, 80000, 120000 abrasive rotations. Before and after all abrasion cycles, the specimens were weighed with an electronic balance with a precision of 10-4 g. The collected data were analyzed using paired samples statistics t-test and ANOVA analysis. Results: All the specimens showed a reduction pattern from the initial weights to weights after 120000 abrasive rotations. With more abrasive rotations, greater weight reduction occurs and this is of statistical significance. ANOVA analysis showed no significant difference between the three types of composites yet, the z250 and Heliomolar groups were associated with the least and the greatest amount of wear, respectively. Conclusions: In all specimens, significant weight reduction occurred after abrasion but there were no significant differences between the 3 types of composites.